Penggunaan Media Komik dalam Meningkatkan Kemampuan Menulis Karangan Narasi Siswa Sekolah Dasar - Desy Mimi Syafitri; Siti Masyithoh (EduInovasi: Journal of Basic Educational Studies, 2024)
The significance of creating grade school understudies' story paper composing abilities using acquiring media, particularly comic media. Indonesian is a language that should be shown in schools, and composing is an essential piece of the language educational experience. Be that as it may, numerous understudies experience hardships recorded as a hard copy story expositions, which can influence how they might interpret the language. It is trusted that the utilization of comic media as a learning device can expand understudies' advantage in learning and assist them with defeating troubles recorded as a hard copy. The exploration was done utilizing a subjective methodology, noticing straightforwardly in the field and gathering information from logical writing. The exploration results show that the utilization of comic media in figuring out how to compose account papers can further develop understudies' composing abilities, animate their creative mind, and make learning more tomfoolery and understudy focused. The examination stages incorporate preparation, execution, perception and reflection, which mean to keep on further developing learning until it accomplishes the ideal objectives